Engineering of acyl ligase domain in non-ribosomal peptide synthetases to change fatty acid moieties of lipopeptides - Rina Aoki; Eri Kumagawa; Kazuaki Kamata; Hideo Ago; Naoki Sakai; Tomohisa Hasunuma; Naoaki Taoka; Yukari Ohta; Shingo Kobayashi (Communications Chemistry)
Abstract Cyclic lipopeptides (CLPs) produced by the genus Bacillus are amphiphiles composed of hydrophilic amino acid and hydrophobic fatty acid moieties and are biosynthesised by non-ribosomal peptide synthetases (NRPSs). CLPs are produced as a mixture of homologues with different fatty acid moieties, whose length affects CLP activity. Iturin family lipopeptides are a family of CLPs comprising cyclic heptapeptides and β-amino fatty acids and have antimicrobial activity. There is little research on how the length of the fatty acid moiety of iturin family lipopeptides is determined. Here, we demonstrated that the acyl ligase (AL) domain determines the length of the fatty acid moiety in vivo. In addition, enzyme assays revealed how mutations in the substrate-binding pocket of the AL domain affected substrate specificity in vitro. Our findings have implications for the design of fatty acyl moieties for CLP synthesis using NRPS.